(untitled) (TEST Ticontre. Theory Text Translation, 2025)
Werner Kofler’s play Tanzcafé Treblinka, premiered at the Klagenfurt Municipal Theatre on 12th May 2001, explores memory and oblivion of the Shoah in Austria. The drama consists of two speeches that follow one another without leaving room for dialogue. In the first, an elderly performer (A) recounts his remembrances of National Socialism and the Final Solution to a young man (B). In the second monologue, B denies the reported information. In developing his exposition, the character seems to possess historical knowledge, although he has no intention of remembering past events. The title of the work hints at Ernst Lerch’s biography, a post-war manager of a family business in Klagenfurt who was responsible for the mass extermination in the General Government during the early forties. Moreover, it calls to mind forgetfulness blended with entertainment (Tanzcafé) and memory of Nazi crimes (Treblinka).